Minimally invasive techniques as adjuncts in low- versus high-lying retained rectal foreign bodies of autoerotic nature in young men: a tailored management algorithm with two contrasting case reports from India - Shubham Kumar Gupta; Vivek Kumar Katiyar; Sumit Sharma; Shashi Prakash Mishra; Satyanam Kumar Bhartiya (Journal of Trauma and Injury)
Retained rectal foreign bodies (RFBs) of an autoerotic nature represent an emerging and rare surgical emergency, posing a sensitive challenge for surgeons. RFBs exhibit a wide range of presentations and require varied management approaches, with the choice of treatment modality differing from case to case. Recently, minimally invasive techniques have been employed for the retrieval of RFBs. In 2021, the World Society of Emergency Surgery and the American Association for the Surgery of Trauma released guidelines on anorectal emergencies, highlighting the usefulness of these techniques as adjunctive tools for both diagnosis and ruling out associated complications. In this report, we describe two noteworthy cases of men who presented to the trauma emergency department with foreign bodies lodged in their rectums. We also highlight the potential role of minimally invasive techniques within a “step-up” approach for the management of retained RFBs.